Draft genome sequence of Vitellibacter vladivostokensis KMM 3516T: A protease-producing bacterium - Thevarajoo, S.; Selvaratnam, C.; Chan, Kok Gan; Goh, K.M.; Chong, C.S. (Elsevier, 2015)
Type strain Vitellibacter vladivostokensis KMM 3516T (=NBRC 16718T) belongs to the phylum Cytophaga-Flavobacterium-Bacteroides. To date, no genomes of the Vitellibacter spp. have been reported, and their metabolic pathways are unknown. This study reports the draft genome sequence of V. vladivostokensis. Moreover, mining of genes associated with proteolytic enzymes was performed to provide insights for further enzyme characterization.